Law Enforcement of Agricultural Commodity Circulation in the Perspective of State Revenue - Yose Rizal; Fadlan Fadlan; Christiani Prasetiasari; Harry Kurniawan (Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Purpose: The purpose of this research is to determine the legal arrangements for the circulation of agricultural commodities from the perspective of state revenue and how the implementation, obstacle factors, and law enforcement solutions for the circulation of agricultural commodities from the perspective of state revenue. Methodology: The research method of this journal is normative juridical (legal research) through a literature study with an empirical juridical approach (sociological juridical) through a field study that aims to empirically obtain legal knowledge. Result: The results showed that the legal regulation of the circulation of agricultural commodities from the perspective of state revenue, namely Article 86, regulates the act of entering the carrier media by not completing the health certificate, through the place of entry determined by the Central Government, or not reporting or not submitting the Carrier Media as regulated in Article 33 of Law Number 21 of 2019. Conclusion: The enforcement of residence permit regulations by the Immigration Office has contributed to upholding national sovereignty and legal order. Despite obstacles, consistent legal enforcement and inter-institutional synergy strengthen the effectiveness of immigration supervision. Limitations: This study is limited to one immigration office and may not reflect the broader national immigration enforcement landscape. Contribution: This research provides insight into practical implementation of immigration law at the regional level and offers recommendations for strengthening law enforcement mechanisms against residence permit violations by foreign nationals.